Investment trade and development issues in the Caribbean - McIntyre, Arnold ([West Indian Commission] [St. Michael]BB, 1991)
Gives a description of the region's export performance, and analyzes the impact of 'supply influences' on export development. Evaluates the regime of export incentives drawing on lessons of the East Asian NIE's. Draws general policy conclusions for the development of exports in CARICOM countries.